A modified Bonora damage model for temperature and strain rate-dependent materials in hot forging process. (August 2020) - Liu, Jiaqi; Chen, Xuewen; Du, Kexue; Zhou, Xudong; Xiang, Nan; Osaka, Akiyoshi
Highlights: A GA-based inverse technique is used to identified the material damage parameters. A new damage model is established considering the temperature and strain rate. Digital image correlation results express the good accuracy of the damage model. Abstract: The initiation and propagation of damage are sensitive to temperature and strain rate, especially for ultra-super-critical rotor steel with high strength at elevated temperature, which probably leads to premature failure in the hot forming process. To accurately describe the damage behavior, a novel damage model incorporating temperature and strain rate was proposed based on Bonora damage model. To establish this damage model, a GA (genetic algorithm)-based inverse method was designed for identifying four damage parameters in Bonora damage model by correlating experimental and simulation data in the tensile tests at elevated temperatures and different strain rates. And then these damage parameters as functions of temperature and strain rate were determined. The proposed damage model was integrated into a finite element software FORGE to simulate the damage evolution of a notched upsetting specimen and the hot tensile specimens. The damage from compressive to tensile states and the fracture behavior were properly predicted, respectively. Additionally, the digital image correlation (DIC) technique was employed to capture the crack initiation and propagation on a flate notched X12 ultra-super-critical rotor steel specimen, which were compared with simulation results to further verify the accuracy of the proposed damage model.